Characterization of Retinal Functionality at Different Eccentricities in a Diurnal Rodent - Escobar, María-José; Reyes, César; Herzog, Rubén; Araya, Joaquin; Otero, Mónica; Ibaceta, Cristóbal; Palacios, Adrián G. (Frontiers in Cellular Neuroscience, 2018)
Although the properties of the neurons of the visual system that process central and peripheral regions of the visual field have been widely researched in the visual cortex and the LGN, they have scarcely been documented for the retina. The retina is the first visual step to integrate optical signals and already includes mechanisms that extract spatio-temporal features needed for animal behavior and survival. Despite considerable efforts to functionally characterize the different types of retinal ganglion cell (RGCs), a clear account of the particular functionality of cells with central vs. peripheral fields is still wanting. Here, we use electrophysiological recording, gathered from retinas of the diurnal rodent, Octodon degus, to show that RGCs with peripheral receptive fields are larger, faster and have shorter transient responses, which translates into greater sensitivity at high temporal frequencies and a full frequency bandwidth, than neurons with more central receptive fields. We also observed that imbalances between ON and OFF cell populations are preserved with eccentricity. Finally, the high diversity of functional types of RGCs in the retina highlights the complexity of the computational strategies implemented at the early stages of visual processing, which could inspire the development of bio-inspired artificial systems.